A description of ligand field effects in the Di-μ-Azido-Bis [{Azido(N,N-diethylethylenediamine)}Copper(II)] compound by the simple overlap model - Malta, O. L.; Mauro, A. E. [UNESP]; Mattioli, M. P D [UNESP]; Sargentelli, V.; Brito, H. F. (FapUNIFESP (SciELO), 1998)
We present a theoretical description of ligand field effects in the di-μ-azido- bis[{azido(N,N-diethylethylenediamine)} copper(II)] compound by the Simple Overlap Model. The ligand field Hamiltonian is expressed in terms of irreducible tensor operators for an assumed D3h site symmetry occupied by the copper ion. The ligand field parameters, calculated from the available structural data, indicate that the copper ion is under the influence of a very strong ligand field. The energy of the d-d absorption band is well reproduced phenomenologically by the model.
Keywords: Amine ligands; Complexes; Copper(II); Ligand field